Economic value creation from nickel downstream processing in Indonesia: Evidence from input–output and empirical value-added estimation - Harimurti, Ivan Krishna; Akbar, Ikhsantino; Pratama, Kristian Abillio (Educoretax, 2026)
Indonesia has promoted nickel downstream industrialization to enhance structural transformation and increase domestic value creation. As the world’s largest nickel producer, the country aims to shift from raw ore exports toward processed products to capture greater economic benefits. However, quantitative evidence on the magnitude of value added at both sectoral and product levels remains limited. This study measures the economic value added of nickel downstream processing using a dual approach. First, an input–output analysis evaluates backward linkages, forward linkages, and value-added multipliers across nickel-related sectors. Second, empirical calculations estimate value added from processing nickel ore into Nickel Pig Iron (NPI) and nickel matte. The results show that the non-ferrous basic metal industry functions as a key sector, with linkage indices above unity and the highest value-added multiplier (2.696). At the product level, NPI generates a value added of US$ 794.40 per ton (109% increase over raw ore equivalent), while nickel matte generates US$ 868.36 per ton (11% increase). These findings confirm that downstream processing enhances economic value, although gains vary across products, underscoring the importance of strategic product prioritization.